Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1073/pnas.89.20.9794
|View full text |Cite
|
Sign up to set email alerts
|

The path of carbon in photosynthesis: improved crop yields with methanol.

Abstract: Foliar sprays of aqueous 10-50% methanol increased growth and development of C3 crop plants in arid environments. The effects of low levels (<1 ml per plant) of methanol were observed for weeks after the brief time necessary for its rapid metabolism. Within several hours, foliar treatment with methanol resulted in increased turgidity. Plants treated with nutrient-supplemented methanol showed up to 100% increases in yields when maintained under direct sunlight in desert agriculture. In the shade and when winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
140
4
5

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 12 publications
(22 reference statements)
11
140
4
5
Order By: Relevance
“…Three applications of 10% methanol increased growth rate and yield of tomatoes without any symptoms of phytotoxicity to leaves. Nonomura & Benson's ( 1992) data supported the hypothesis that the increase in growth was because of an inhibition of photosynthate loss as a result of photo-respiration. Ethanol has also been shown to have effects in plant tissues, often associated with ethylene activity (Heins H93086 Received 17 December 1993;accepted 17 June 1994accepted 17 June 1980Saltveit 1989;Wu et al 1990;Mencarelli 1991) and on stomatal resistance by its effect on removing leaf resin (Meinzier et al 1990).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Three applications of 10% methanol increased growth rate and yield of tomatoes without any symptoms of phytotoxicity to leaves. Nonomura & Benson's ( 1992) data supported the hypothesis that the increase in growth was because of an inhibition of photosynthate loss as a result of photo-respiration. Ethanol has also been shown to have effects in plant tissues, often associated with ethylene activity (Heins H93086 Received 17 December 1993;accepted 17 June 1994accepted 17 June 1980Saltveit 1989;Wu et al 1990;Mencarelli 1991) and on stomatal resistance by its effect on removing leaf resin (Meinzier et al 1990).…”
Section: Introductionsupporting
confidence: 81%
“…The methanol growth stimulation data, although not of the same magnitude, agrees with that of Nonomura & Benson (1992). This may have been because no wetting agent or nitrogen supplementation was used in our experiment.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that foliar application of methanol can stimulate plant growth (Nonomura and Benson, 1992) and that methanol is quickly oxidized in most plant tissues successively to formaldehyde, formic acid, and CO 2 (Cossins, 1964). Formaldehyde can be incorporated to plant C1 metabolism mainly by two metabolic pathways that involve folatemediated and -independent reactions (Hanson and Roje, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Makela et al (1998) stated that the Glycinebetaine, product from sugar beet, is (Mweresa et al 2014). Releasing of CO 2 from fermentation of molasses creates an additional carbon source to the plant (Quan et al 2005) and thus, photorespiration rate of the plants reduced and net photosynthesis increase (Nonomura and Benson 1992).…”
Section: şAnlı Ve Ark "Melas Uygulamalarının şEker Pancarında (Beta mentioning
confidence: 99%